DEFENDING WOMEN UPHOLDING NORM: Political Aspiration of Bu Nyai in Indonesian Local Politics - Bahar, Moh. Syaeful; Chalik, Abdul; Riyadi, Abdul Kadir (JOURNAL OF INDONESIAN ISLAM, 2025)
The public and political role of Muslim women in Indonesia has been on the increase in recent years. This is due family connections, gender equality, and religious piety. This article particularly highlights the political participation of Bu Nyai, Muslim personalities with pesantren backgrounds. This paper contends that their motive is their aspiration to advocate women's rights, which is often ignored by male-politicians. The idea that “only women understand women” represents another reason why these Bu Nyai compete in elections for public office. The Bu Nyai relies much on defending values and norms rather than on competence or experience. The wisdom behind this is the fact that Indonesian politics is not always about idea, as it is about sense and positive image. These are the so-called social and spiritual capitals that this paper tries to explore by referring to three Bu Nyai in East Java and their political aspiration in upholding norms by defending women. The rise of these Bu Nyai and their prominence in local elections is a direct testimony that Indonesian politics is not patriarchal. Their activism is an automatic repudiation of neo-liberal thesis that in major Muslim societies, women are politically marginalized.